Neuropathology and immune biomarker discovery in a rat model of Alzheimer's disease, TgF344‐AD, with controlled cortical injury model of traumatic brain injury: Development of new models and analysis methods/neuroinflammation. (7th December 2020) - Wang, Athena Ching‐Jung; Adame, Vanesa; Markham, Neil; Potter, Huntington; Boyd, Timothy
Abstract: Background: Individuals with a history of traumatic brain injury (TBI) have a higher risk of developing Alzheimer's disease (AD) and AD‐related dementias (ADRD), such as chronic traumatic encephalopathy (CTE). However, the relationship(s) between TBI, AD, and CTE remain poorly understood and markedly understudied. Because transgenic mouse models of AD that develop amyloidosis do not readily develop pathological tauopathy that is commonly found in ADRD, we used the TgF344‐AD transgenic rat model of AD in which amyloid deposition drives endogenous tauopathy and neurodegeneration for our TBI studies. Method: We used the closed‐head controlled cortical impact (CCI) model of TBI, performed either once (1X‐CCI) or twice over two weeks (2X‐CCI) in both 6‐ and 12‐month‐old TgF344‐AD and wild‐type (F344) rats to investigate the effects of TBI on acute and chronic neuroinflammation, on blood brain barrier (BBB) integrity, and on ADRD‐associated neuropathology. Whole brains and terminal blood draws were collected at different time points following the 1X‐ or 2X‐CCI TBI procedures at 3, 15, 30, 60, and 120 days after the final CCI procedure. Thus, the tissue collection ages of animals across the project allow for TBI‐induced ADRD‐related pathological analyses at 6, 7, 8, 10, 12, 13, 14, and 16 months of age. MRI scans were conducted at 30‐days post‐CCI to examine BBB leakage and chronic inflammation, with subsequent post‐mortem histochemical confirmation. Terminal blood draw samples were used for complete blood cell counts with differential and multiple biomarker analyses. Result: This project is ongoing, but interim analyses reveal chronic neutrophil percentages remaining consistent in both TgF344‐AD and wild‐type 12‐month‐old cohorts undergoing either 1X‐ or 2X‐CCI at all post‐injury time points. Also, the upright time for the animals does not appear to differ based on impact type or genotype so far. However, histochemical pathological analyses of the 12‐month‐old AD rats have demonstrated changes in Aβ pathology and astrogliosis markers. MRI analyses have not yet been completed. Conclusion: We are continuing to carry out detailed analyses of changes in ADRD‐related pathology and blood biomarkers. These animal models should help provide an increased understanding of chronic neuroinflammation and other pathological mechanisms associated with TBI and risk for ADRD.